Adapting the Parental Mediation Scale into Turkish and Analyzing It According to Various Variables - Gür, Duygu; Türel, Yalın Kılıç (T.C. Milli Egitim Bakanligi, 2025)
It is critical for children to maximize the opportunities in digital environments while minimizing the risks and dangers in these environments. The approaches, behaviors, and strategies displayed by parents have a determining role in children’s use of technology in this process. Researchers are interested in the roles and strategies that parents take on; this is known as parental mediation. The purpose of this study is to translate the “Parental Mediation” scale into Turkish, identify parents’ mediation, and analyze it using different variables. Firstly, we carried out studies on adapting the scale to Turkish, and then we analyzed the results by applying the prepared scale form to parents. In accordance with the advice of experts, we translated the scale items into Turkish. Then, we applied it to 318 parents of sixth and seventh grade students and conducted a confirmatory factor analysis (CFA). According to the results, the scale’s fit levels were sufficient and provided convergent reliability and convergent validity. Additionally, by calculating the Cronbach Alpha reliability coefficient, we determined that the scale and each factor were reliable. Therefore, it may be concluded that a valid and reliable scale has been provided to the field. The results revealed that parents had more restrictive mediation approaches than active mediation, but they also communicated and informed their children. Parental mediation also differed significantly depending on how parent and their children used technology. We believe that the research findings may contribute to the measures to be taken and activities to be carried out within the framework of school-family cooperation in children’s use of technology. © (2025), (T.C. Milli Egitim Bakanligi). All rights reserved.
Ebeveyn Arabuluculuğu Ölçeğinin Türkçeye Uyarlanması ve Çeşitli Değişkenler Açısından İncelenmesi*
Keywords: digital opportunities; digital parenting; dijital ebeveynlik; dijital fırsatlar; ebeveyn arabuluculuğu; online risks; parental mediation; scale adaptation; çevrim içi riskler; ölçek uyarlama